2006
DOI: 10.1158/0008-5472.can-06-1629
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of Heat Shock Protein 27 Induces Resistance to 17-Allylamino-Demethoxygeldanamycin through a Glutathione-Mediated Mechanism

Abstract: 17-Allylamino-demethoxygeldanamycin (17-AAG), currently in phase I and II clinical trials as an anticancer agent, binds to the ATP pocket of heat shock protein (Hsp90).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
152
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(161 citation statements)
references
References 49 publications
(59 reference statements)
8
152
1
Order By: Relevance
“…We observed a significant increase in hsp22, hsp27, and hsp70 expression in the flies that were exposed to DCA up to 48 h. However, in flies that were exposed to DCA for a prolonged period, hsp27 expression was significantly upregulated in 30-50-dayold organism. hsp27 is reported to maintain cellular redox by upholding intracellular glutathione (Arrigo et al 2005;Concannon et al 2003;McCollum et al 2006) and by suppressing ROS generation (Liu et al 2007;Wyttenbach et al 2002). In agreement with the above discussion, we observed decreased ROS generation and GSH depletion concurrent with increased hsp27 expression in DCA-exposed aged flies which was further evident by a significant positive correlation drawn between hsp27 expression and GSH content (Y GSH =0.592 hsp27 +0.341, r=0.847, P=0.033) and a Fig.…”
Section: Discussionsupporting
confidence: 90%
“…We observed a significant increase in hsp22, hsp27, and hsp70 expression in the flies that were exposed to DCA up to 48 h. However, in flies that were exposed to DCA for a prolonged period, hsp27 expression was significantly upregulated in 30-50-dayold organism. hsp27 is reported to maintain cellular redox by upholding intracellular glutathione (Arrigo et al 2005;Concannon et al 2003;McCollum et al 2006) and by suppressing ROS generation (Liu et al 2007;Wyttenbach et al 2002). In agreement with the above discussion, we observed decreased ROS generation and GSH depletion concurrent with increased hsp27 expression in DCA-exposed aged flies which was further evident by a significant positive correlation drawn between hsp27 expression and GSH content (Y GSH =0.592 hsp27 +0.341, r=0.847, P=0.033) and a Fig.…”
Section: Discussionsupporting
confidence: 90%
“…The role of MSCV integration in making the cells more viable in the presence of GA remains unclear, although we did observe a slightly enhanced amount of total glutathione (data not shown). This may account for resistance of the MSCV cells to geldanamycin based on a previous study which showed a correlation between increased glutathione levels and resistance of cells to Hsp90 inhibitors [22].…”
Section: Resultsmentioning
confidence: 85%
“…Thus, it is likely that STAT5 modulates expression or activity of these enzymes via an indirect effect on Hsp27 and Hsp70 expression. 43,44 In addition to these proteins, DJ-1, originally identified as an oncogene product, is a protein with anti-apoptotic activity and its main action is to protect cells from oxidative stress. 33 DJ-1 plays a major role in the removal of hydrogen peroxide, a powerful oxidant 33 and in the protection against oxidative stress by increasing intracellular levels of GSH and Hsp70.…”
Section: Discussionmentioning
confidence: 99%